Village Baseline Study: Site Analysis Report for Kollo – Fakara, Niger (NI0111) - Goudou D; Traoré Gue, J.N.; Ouédraogo, Mathieu; Segda, Zénabou; Baye YA; Mamoudou H; Boureima, Moussa; Zougmoré, Robert B.; Moussa, Abdoulaye S. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
The village baseline study of Tigo Zéno village in the CCAFS benchmark site Fakara in Niger took place from 23 to 25 of June 2011. Focus group discussions were conducted separately for men and women. Tigo Zéno’s natural resources are degraded, with sparse tree population. Water is scarce and temporary, the farmlands have eroded, and soil is infertile with low productivity. People are particularly concerned about the presence and expansion of gullies (“koris”) that have created uncultivable areas, major declines in soil fertility, destruction of crops during serious overflow of ponds and heavy rainfall, and significant reduction in the size of farmlands, especially those belonging to women, who have smaller farmlands than men.